2000
DOI: 10.1021/cm990704b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Mesogenic Disklike Benzenetricarboxylates Containing Diacetylenic Groups and Their Polymerization

Abstract: Polymerizable disklike compounds that have a benzene ring core and three rigid diacetylenic units were prepared. The diacetylenic units were attached to the benzene ring via ester linkages. By varying number of alkoxy tail carbons and benzene rings of the disk, the morphological change of the compounds and their polymerization were investigated by differential scanning calorimetry (DSC), polarizing optical microscopy, infrared spectroscopy (IR), and powder X-ray diffraction (XRD). Compound 7 with no alkoxy tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 27 publications
1
39
0
1
Order By: Relevance
“…In contrast, 4 has an asymmetrical structure, and it exhibits two absorptions at 2160 and 2200 cm À1 from the symmetric and asymmetric stretching vibrations of the C C bonds, respectively. This observation is consistent with the fact that the IR spectra of asymmetrical diacetylenes exhibit two absorptions for ñ(C C), as reported previously [14].…”
supporting
confidence: 93%
“…In contrast, 4 has an asymmetrical structure, and it exhibits two absorptions at 2160 and 2200 cm À1 from the symmetric and asymmetric stretching vibrations of the C C bonds, respectively. This observation is consistent with the fact that the IR spectra of asymmetrical diacetylenes exhibit two absorptions for ñ(C C), as reported previously [14].…”
supporting
confidence: 93%
“…[22,23] Molecules of the first group are also called mesogen trimers. This term is, however, not sufficiently precise, since linear, branched and bent trimers exist.…”
Section: Classification and Motivationmentioning
confidence: 99%
“…4-Trimethylsilylethynylphenol and 4-ethynylphenol were prepared according to our previous report. 17 Bromine (39.9 g, 0.25 mol) was added to a vigorously stirred solution of potassium hydroxide (37.5 g) in water (100 mL) with cooling at 0 o C. 18 1-Hexyne (0.15 mol) in dioxane (80 mL) was added dropwise to the above mixture over 2 h. The reaction mixture was stirred for 40 h without further cooling. Then the mixture was extracted with chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…12 It was reported that in a liquid crystalline state, the 1,4-polymerization also occurred to give highly ordered polymers. [13][14][15][16][17] In this work, we prepared a linear rod-like molecule, consisting of two diacetylenic groups, and examined its UV polymerization in the solid state. Thin films of the monomer were prepared by a physical vapor deposition or solution casting method.…”
Section: Introductionmentioning
confidence: 99%